Artificial Intelligence and Fake News - Hussein , Fadia; Hejase, Hussin J. (Žurnalistikos tyrimai, 2023)
Artificial intelligence depends on digital devices’ performance to perform tasks regularly, requiring human intelligence, using special software to accomplish work easier and faster, carrying out data-packed tasks, and providing useful analytics or solutions. It also requires a specialized laboratory that provides high-performance computing capabilities and a technical platform for deep machine learning. These resources will enable the artificial intelligence platform to master the machine learning techniques of using, developing, simulating, predicting models, and building ready-to-use technological solutions such as analytics platforms.In general, the artificial intelligence system manipulates and manages large amounts of training data to form correlations and patterns used in building future predictions . A limited-memory artificial intelligence system can store a limited amount of information based on the data that have been processed and dealt with previously to build knowledge by memory when combined with pre-programmed data. Consequently, one may ask how artificial intelligence applications contribute to verifying the truthfulness of the media through digital media. How do they contribute to preventing the spread of misleading and false news?This study tries to answer the following question: What methods and tools are adopted by artificial intelligence to detect fake news, especially on social media platforms and depending on artificial intelligence laboratories?This paper is framed within automation control theory and by defining the needed control tools and programs to detect fake news and verify media facts.